The theoretical crisis of trust in science is becoming science's practical crisis: Perspective through the eyes of citations - Jaime A. Teixeira da Silva (National Scientific Medical Center, 2024)
The claimed crisis in science has many origins that, when observed uniquely, might got give the impression of a widespread problem. However, when their integrated networks are appreciated, the crisis then begins to take on a form and life of its own. This letter looks at the basis for a potential crisis in any field of research through the prism of citations, specifically the citation of articles that may become invalidated through retraction, or whose integrity may be weakened through an associated expression of concern (EoC). Fields of research, or bodies of literature of individual researchers, that are weakened by an excessive volume of retractions or EoCs face intellectual and scientific implosion.